Whitefly-Transmitted Cucurbit Leaf Crumple Virus in Florida - Susan E. Webb; F. Akad; Teresia W. Nyoike; Oscar E. Liburd; Jane E. Polston (EDIS, 2007)
ENY477, a 3-page illustrated fact sheet by S. E. Webb, F. Akad, T. Nyoike, O. E. Liburd, and J. E. Polston, describes a begomovirus new to Florida which was discovered on squash in north central and northeast Florida in November 2006. It includes a brief discussion of identification and control measures and references cited. Published by the UF Department of Entomology and Nematology, March 2007.